HYPERREALITY AND SIMULACRA OF SOCIAL MEDIA IN AL RAWABI SCHOOL FOR GIRLS SERIES - Faz, Najma Tsuroyya; Mustofa, Arif (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
In the digital era, social media significantly shapes adolescent identity by creating hyperreal representations that blur the boundaries between reality and simulation. This study aims to analyze how social media simulacra are depicted in Al Rawabi School for Girls Season 2 and their impact on adolescents. Using a qualitative approach, six episodes were analyzed through Jean Baudrillard’s four stages of images: reflection of image, denatures of image, absence of image, and no relation of image. The results show that denatures of image stage is most dominant, revealing how digital image manipulation affects teenagers perception, behaviors, and social interactions. The hyperreality of social media contributes to bullying, suicide, identity distortion, and consumptive banality among teenagers. This study contributes to research on modern Arab media and culture by applying postmodern theories of simulacra and hyperreality to contemporary youth media, providing insight into how digital images and social validation shape teenagers' identity.